Efficiency and Expense Preference in the Philippines' Cooperative Rural Banks - Mario B. Lamberte; Martin Desrochers (Philippine Institute for Development Studies (PIDS), 2002)
This paper attempted to test whether efficient cooperative rural banks (CRBs) have a better control of their agency costs. We used two different concepts of efficiency, namely, cost efficiency and alternative profit efficiency, and found somewhat different results from both approaches. Using Stochastic Frontier Approach and Distribution Free Approach, we tested two different propositions. The first proposition is that an adequate corporate governance scheme should improve efficiency of CRBs. We failed to find very conclusive evidence that corporate governance theories apply to the Philippines CRBs. However, the results confirmed both managers compensation theory and large stakeholders theory. The second proposition is that agency costs should reduce efficiency of CRBs, and we found a much clearer relationship on that issue. As expected, most efficient CRBs are characterized by a better control of agency costs. These results are in accordance with previous studies on shirking behavior among mutual financial intermediaries. We also found that rural CRBs are most profit efficient, despite their somewhat normal cost-efficiency, a manifestation that they are able to charge higher fees for the quality of services they offer. Large CRBs are not able to pass their higher costs to customers through higher fees. We found that small CRBs might have a better interest rate policy, that is, they offer lower rates on both loans and deposits.
Keywords: 330; agency costs; corporate governance; efficiency; Ländliches Finanzsystem; Genossenschaftsbank; Bank; Effizienz; Transaktionskosten; Corporate Governance; Philippinen